"Beet-ing" the mountain: A review of the physiological and performance effects of dietary nitrate supplementation at simulated and terrestrial altitude - Shannon, O. M.; McGawley, K.; Nybäck, L.; Duckworth, L.; Barlow, M. J.; Woods, D.; Siervo, M.; O`Hara, J. P. (Sports Medicine, 2017)
Exposure to altitude results in multiple physiological consequences. These include, but are not limited to, a reduced maximal oxygen consumption, drop in arterial oxygen saturation, and increase in muscle metabolic perturbations at a fixed sub-maximal work rate. Exercise capacity during fixed work rate or incremental exercise and time-trial performance are also impaired at altitude relative to sea level. Recently, dietary nitrate (NO3-) supplementation has attracted considerable interest as a nutritional aid during altitude exposure. In this review, we summarise and critically evaluate the physiological and performance effects of dietary NO3- supplementation during exposure to simulated and terrestrial altitude. Previous investigations at simulated altitude indicate that NO3- supplementation may reduce the oxygen cost of exercise, elevate arterial and tissue oxygen saturation, improve muscle metabolic function, and enhance exercise capacity/performance. Conversely, current evidence suggests that NO3- supplementation does not augment the training response at simulated altitude. Few studies have evaluated the effects of NO3- at terrestrial altitude. Current evidence indicates potential improvements in endothelial function at terrestrial altitude following NO3- supplementation. No effects of NO3- supplementation have been observed on oxygen consumption or arterial oxygen saturation at terrestrial altitude, although further research is warranted. Limitations of the present body of literature are discussed, and directions for future research are provided.